How reliable is classic chest radiography in the diagnosis of small pleural effusion - Kocijančič, Igor (Radiology and oncology (Ljubljana), 1999)
Purpose. To evaluate the usefulness of expirium lateral decubitus views in theradiological diagnosis of small pleural effusions. Materials and methods. Patients referred to abdominal sonography for different reasons were routinelychecked for possible pleural effusion. From November 1994 till May 1996, 36 such patients were found to have pleural effusion not exceeding 15 mmand were included in the study. Patients were examined radiologically in erect PA and lateral projections and, after 5 min. in decubitus position, in inspiratory-expiratory lateral decubitus projections with 10 hip elevation andcentral beam on the lateral chest wall. Results. In 22 out of 36 patients (61 %), the pleural fluid was not visible on erect PA and lateral chest radiogram. However, the fluid was visible in 35/36 patients (97%) in expirium from lateral decubitus view. The average thickness of fluid from lateral decubitus views in inspirium and expirium was 4.3 and 7.9 mm, respectively. In31 out of 36 patients (86%), the thickness of the fluid layer as measured inexpirium and inspirium was different. In 16%, the fluid was not visible on inspirium lateral decubitus projections. Conclusions. Radiography turned out to be almost as sensitive as sonography in detection of small pleural effusions. Lateral decubitus views taken in expirium contributed essentially to the diagnostic sensitivity in our study.
Keywords: Diagnosis; Pleural effusion; Radiography; Thoracic radiography